Antigen-Presenting Cells and Antigen Presentation in Tertiary Lymphoid Organs - Hughes, Catherine E.; Benson, Robert A.; Bedaj, Marija; Maffia, Pasquale (Frontiers in Immunology, 2016)
Tertiary lymphoid organs (TLOs) form in territorialized niches of peripheral tissues characterised by the presence of antigens; however, little is known about mechanism(s) of antigen handling by ectopic lymphoid structures. In this mini review, we will discuss the role of antigen presenting cells and mechanisms of antigen presentation in TLOs, summarizing what is currently known about this facet of the formation and function of these tissues, as well as identifying questions yet to be addressed.